Pre and per operative prediction of difficult laparoscopic cholecystectomy using clinical and ultrasonographic parameters - Gupta, Gaurav; Sharma, Pranav Kumar; Gupta, Sangita; Bhardwaj, Ankit (International Journal of Research in Medical Sciences, 2017)
Background: Cholecystectomy is the procedure of choice for symptomatic gall stones. Laparoscopic Cholecystectomy (LC) may be rendered difficult by various problems encountered during surgery. Several factors have been implicated with a difficult case, but no reliable criteria are available yet to identify patients preoperatively with a difficult LC. Preoperative prediction of a difficult LC can help the patient as well as the surgeon prepare better for the intraoperative risk and the risk of conversion to open cholecystectomy. The present study was undertaken to evaluate role of various factors responsible for conversion from laparoscopic to open cholecystectomy and also to study the intraoperative problems faced by the surgeon responsible for conversion in order to make the procedure safer for the patient as well as the surgeon. Methods: In 50 consecutive patients who underwent LC during 2013 to 2014 patient’s characteristics, clinical history, laboratory data, ultrasonography results and intraoperative details were prospectively analyzed to determine predictors of difficult LC. Results: Of 50 patients 3 (06%) required conversion to open cholecystectomy. Significant predictors of conversion were obscured anatomy of Calot’s due to adhesions, sessile gall bladder, male gender and gall bladder wall thickness >3 mm. Conclusions: With preoperative clinical and ultrasonographic parameters, proper patient selection can be made to help predict difficult LC and a likelihood of conversion to open cholecystectomy.